The effect of concussion history on cognitive-motor integration in elite hockey players - Hurtubise, J.; Gorbet, D.; Hamandi, Y.; Macpherson, A.; Sergio, L. (Concussion, 2016)
Aim: To observe the effects of concussion history on cognitive-motor integration in elite-level athletes. Methods: The study included 102 National Hockey League draft prospects (n = 51 concussion history [CH]; n = 51 no history [NC]). Participants completed two computer-based visuomotor tasks, one involved `standard` visuomotor mapping and one involved `nonstandard` mapping in which vision and action were decoupled. Results: We observed a significant effect of group on reaction time (CH slower) and accuracy (CH worse), but a group by condition interaction only for reaction time (p < 0.05). There were no other deficits found. We discussed these findings in comparison to our previous work with non-elite athletes. Conclusion: Previously concussed elite-level athletes may have lingering neurological deficits that are not detected using standard clinical assessments.